C-X-C motif chemokine ligand 13 suppresses osteoclast differentiation via interference with RANKL–RANK interaction - Ho, Trung-Loc; Lee, Kun-Tsan; He, Yu-Hao; Thuong, Le Huynh Hoai; Achudhan, David; Huang, Wei-Chien; Ko, Chih-Yuan; Liu, Chun-Lin; Guo, Jeng-Hung; Tang, Chih-Hsin (Frontiers in Immunology, 2026)
IntroductionOsteoclastogenesis, the differentiation of osteoclasts from monocyte/macrophage precursors, is essential for physiological bone remodeling but contributes to pathological bone loss in arthritis, osteoporosis, and bone metastasis when dysregulated. CXCL13 is a CXC chemokine well recognized for its role in immune regulation; however, its function in osteoclast biology remains undefined. This study aimed to investigate the effects of CXCL13 on RANKL-induced osteoclastogenesis.MethodsRAW264.7 cells were stimulated with RANKL to induce osteoclastogenesis. Osteoclast formation was evaluated by TRAP and F-actin ring staining, and quantitative real-time PCR (qPCR). GEO bioinformatic analysis revealed gene expression changes during RANKL-induced osteoclastogenesis. Mature osteoclast apoptosis was analyzed by cleaved caspase-3 immunofluorescence staining. MAPK and NF-κB signaling activation was examined by Western blotting and NF-κB luciferase reporter assays. Molecular docking and co-immunoprecipitation were performed to evaluate the interaction between CXCL13 and RANK.ResultsCXCL13 inhibited RANKL-induced osteoclast formation, suppressed osteoclast marker expression, disrupted F-actin ring assembly, and promoted apoptosis in mature osteoclasts. Mechanistically, CXCL13 attenuated MAPK and NF-κB activation and blocked p65 nuclear translocation in a CXCR5-independent manner by competitively interfering with RANKL–RANK binding and downstream RANK–TRAF6 signaling.DiscussionThese findings identify CXCL13 as a novel suppressor of osteoclastogenesis by interfering with RANKL–RANK signaling, unveiling an unrecognized regulatory role in osteoclast biology and suggesting potential therapeutic relevance for bone loss disorders.